Safety measures at rural stop controlled intersection in UMP Gambang - Nurul Fajrina Hazirah, Azman (2017)
This project is a research about safety measures at rural stop controlled intersection in UMP Gambang. The case study was conducted at the main road that are located heading to Kolej Kediaman 2 and Kolej Kediaman 4 from the entrance road of UMP or from highway. The traffic sign and marking data was collected from observation while geometric design data was collected from observation. The information about accident data was collected from Bahagian Keselamatan UMP and the data of traffic volume was gathered from survey. The survey of traffic volume was conducted for 1 day during peak hour which is in morning and evening for 1 hours. The survey includes various mode of transport such as cars, motorbike, buses and others that passing the road according to their classes during summer. Safety level will be assessed according to the warrants. From the research that had been done, the number of accident increases because volume of transportation increases. Most of UMP students have cars and motorcycles the factor that contribute to this phenomena are traffic marking faded, and human behaviour. This is because the road provide confusion as the junction looks straight at every each of the way. Some of the road user does not know which way is the priority while the others just do not follow the rules. Besides that, some of the traffic sign is not follow the standard. This may lead the road user ignore the sign and rules. They are not following the rules and based on my observation, they speed more than proposed speed and U-turn at place that U-turn is not allowed. The condition of the traffic marking is also not good because the marking is already faded. This provide confusion to the road user as the road is design to give way but the road user does not aware of the faded road marking. As there are many accident happened there, the barricades is used to overcome this problems, however, there are still accident happened because road user do not comply with the laws of the road. Based on the geometric data, Summary of Specific Factors and Form of Intersection Control Choice. (Sources: Safety and Operational Assessments conducted by Alberta Transportation) are referred to determine suitable level of intersection for this intersection. From the results, roundabout is the most suitable for this intersection.